Komparasi Financial Teknologi Syariah di Negara Indonesia dan Malaysia - Saputra, Randa Fajar; Y, Yusra; S, Syahpawi (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Verse 133 of Surah Al-Baqarah in the Koran reflects an important moment in history when the prophet Yakub (Jacob) was nearing the end of his life and spoke to his children about their spiritual choices after his death. (133) Were you witnesses when death came to Jacob, when he said to his sons, "What will you worship after I die?" They answered, "We will worship your God and the God of your ancestors, namely Abraham, Ishmael and Isaac, (namely) God Almighty and we (only) surrender to Him." This verse describes the strong testimony of the descendants of Ibrahim (Abraham), Ismail (Ishmael), and Ishaq (Isaac) about their loyalty to Allah Almighty. They vowed to continue worshiping Allah and continuing the divine legacy that had been passed down by their ancestors. This paper will outline the historical context of this verse, the deep meaning of loyalty to one God, and the universal message about faith, devotion, and spiritual continuity in human life. This verse reminds us of the importance of maintaining the legacy of faith and obedience to Allah, which is a strong foundation for a meaningful and blessed life.